Visual Function and Emotional Regulation in Achromatic Color and Chromatic Color using Low Resolution Brain Electromagnetic Tomography Analysis (LORETA) - Sroykham W. (2023)
The chromatic and achromatic colors were processed by photoreceptor cells with rod and cone cells (L-cone cell, M-cone cell, and S-cone cell) in the retina through the visual pathway. This color processing was also known to cause emotional regulation. This study investigated the interrelationship between visual function and emotional regulation by Low Resolution Brain Electromagnetic Tomography Analysis (LORETA). The results of chromatic color illustrated that LORETA absolute power of red color was higher in the left hemisphere at Brodmann area 38-42 (which was a function in emotion processing) more than yellow color, blue color, and green color, respectively. These results were also correlated with the Brunel Mood Scale questionnaire (BRUMS). In achromatic color, LORETA absolute power of white color was higher in the left hemisphere (at Brodmann area 38-42) than in black color. Furthermore, the white color activated the cortical activity at the temporal and frontal lobes higher than the black color. Moreover, the LORETA source correlation in the primary visual cortex (V1; Brodmann area 17), red and yellow colors highly activated the cortical activity at the frontal and temporal lobes. Low cortical activation can be found in the frontal lobe in blue and green colors. However, the visual cortex was not changed significantly during the presence of achromatic and chromatic colors. These results can be used as a recommendation to design the color room for the activation of both positive and negative emotions.